Адміністративно-правовий механізм вдосконалення сертифікації органічної сільськогосподарської продукції - Берлач, Н.А. (Часопис Київського університету права, 2009)
В статье раскрыто содержание административно-правового совершенствования процедуры сертификации органического сельского хозяйства в Украине. Проанализированы главные проблемы в процессе становления данной системы. Обоснован перечень направлений совершенствования содержания и структуры отечественной сертификационной системы. Ключевые слова: органическое сельское хозяйство, сертификация, административно-правовое регулирование, аккредитация, АПК. The article disclosed the contents of the administrative and legal procedures to improve the certification of organic agriculture in Ukraine. Тhe main problems in the process of the system. substantiate the list of areas to improve the content and structure of the national certification system are analyzed. Key words: organic agriculture, certification, administrative and legal regulation, accreditation, AIC.